Under the context of smart agriculture: assessment of agricultural product distribution efficiency in various regions of China - Zheng, Zihao (Frontiers in Sustainable Food Systems, 2024)
The efficient development of the agricultural product circulation industry, as a crucial component of agricultural growth, directly impacts the successful realization of the country’s rural revitalization strategy. Despite the favorable trend in the development of China’s agricultural product circulation industry, with continuous growth in the volume of agricultural product circulation and overall logistics turnover, challenges persist. There remains a prevalent emphasis on “heavy production and light circulation” in agricultural development, leading to high circulation costs and notably low efficiency. This situation necessitates imminent reforms within the agricultural product circulation industry. In response to emerging contradictions in the contemporary agricultural product circulation domain, the country has strategically advocated for digital development. The advancement of next-generation information technology has propelled the reforms within the agricultural product circulation industry and the exploration of intelligent technology applications in this field aligns with practical developmental needs. Firstly, this article constructs an evaluation framework for agricultural product circulation efficiency based on the perspective of dual online and offline circulation channels. Utilizing the data envelopment analysis (DEA) method, the study calculates the static efficiency of agricultural product circulation in China. Through regional comparisons, it is revealed that the overall efficiency of agricultural product circulation is highest in the eastern region, followed by the central and northeastern regions, with the western region lagging behind. Secondly, employing the Malmquist index model, the study investigates the changes in total factor productivity within agricultural product circulation. The findings indicate the following trends during the statistical period: the circulation of agricultural products in the eastern region has maintained a substantial growth rate primarily driven by technological advancements; in the northeastern region, the overall total factor productivity in agricultural product circulation shows an increasing trend but displays an M-shaped variation; the central region witnesses relatively low average annual growth in total factor productivity, characterized by significant fluctuations primarily influenced by variations in pure technical efficiency; the western region experiences a continuous decline in scale efficiency and pure technical efficiency compared to the previous year, with only a rise in technological progress index supporting a slight increase in total factor productivity.